Deviant use of adjectives in speech of polish and kazakh students - Amangeldiyeva, Gulmira (Pedagogy and Psychology, 2021)
The purpose of the article is a comprehensive analysis of deviations in speech depending on close and non-close bilingualism. The author compiled comparison table of grammatical categories of Russian and Kazakh, Russian and Polish languages. As a result of adjective grammatical categories systems comparison the areas of inconsistency are identified: Russian and Kazakh – 5 out of 8, Russian and Polish languages – 2 out of 8. To measure the level of influence of the native language on the studied Russian language, to identify weak sections, to compile diagrams and a comparative analysis of typical deviations, made by Poles and Kazakhs, a survey among students (20 people) has been conducted. On the basis of this experiment, a deep analysis of deviations and errors of Polish and Kazakh audiences has been provided; the errors diagram has been calculated and compiled. Analysis of deviations from the norm is important in terms of mass stability of two (poly) linguistic space. Its results are significant both for theory and for practice. The urgency of the research is specified by queries of the interethnic communication practice, by the order of society, by the concerns of scientists, developing effective methods. The proposed statements are applicable for analysis of any linguistic material, because the model of analysis of negative speech material is universal, which is confirmed by the comparison of deviations of Kazakh-Russian and Polish-Russian bilinguals.